EFFECT OF NPK FERTILIZATION AND FOLIAR APPLICATION OF IRON , GIBBERELLIC ACID ON THE GROWTH AND YIELD OF SALEMY POMEGRANATE CULTIVAR (Punica granatum L.) 2. STUDY THE YIELD AND ITS PHYSIGAL COMPONENTS - Nabil M. Ameen Al-Imam (Mesopotamia Journal of Agriculture)
This investigation had been conducted in an special orchard at Al-Hawija town which belongs to Kirkuk governorate during 2005 and 2006 growing seasons in order to study the effect of NPK fertilizer and foliar application of iron and gibberellic acid (GA3) and their interactions on the growth and yield of Pomegranate (Punica granatum L.) trees CV. Salemy (local variety) .The results are summarized as follows: Addition of NPK fertilizer at 880 kg NPK/Hectare or the spray with the chelat iron (200 mg Fe/l) and with gibberellic acid at 200 mg GA3/l caused significant increments in total yield of tree, number and weight of fruit per tree, weight of 100 berry and juice percentage of berries .The interactions of 880 kg NPK/Hectare +200 mg Fe/l + 200 mg GA3 /l was the best treatment which caused significantly increased in the total yield, number of fruit per a tree, weight and size of 100 berries and the juice percentage of berries for both seasons.